Interpretation Method Of Al-Tafsir Al-Tarbawi Li Al-Qur'an Al-Karim By Anwar Al-Baz: Study Of Surah Al-Muzammil - Nurdin, Aldi; Rohmatulloh, Acep Ihsan; Haririe, Muhammad Ruhiyat; Zulaiha, Eni (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
The study of the methodology of interpretation not only leads us to be able to understand the content of the Qur'an, but more than that we can know the processes and procedures and ways of each mufassir in interpreting the Qur'an. The purpose of this study is to analyze the method of interpretation of al-Tafsir al-Tarbawi li al-Qur'an al-Karim by Anwar Al-Baz. This research belongs to the type of qualitative research based on literature study using a descriptive analysis approach. The results of this study conclude that there are five specific methods applied by Anwar al-Baz in his tafsir, namely maintaining the writing system based on the mushaf, explaining the meaning of mufradat, explaining the procedural purpose of the verse, explaining the content of verses that have relevance to education, and explaining globally the instructions of verses related to education. The aim of the tarbawi interpretation approach brought by Anwar Al-Baz aims to explore the educational values ​​contained in the verses of the Koran, not specifically to form an educational system or methodology.